Adaptive Evaluation of LQR Control using Particle Swarm Optimization for Pendubot - Nguyen, Duc-Anh-Quan; Nguyen, Luu-Quang-Thinh; Nguyen, Phong-Luu; Le, Duc-Quy; Lieu, Phu-Thuan-An; Lam, Quang-Buu; Tran, Anh-Thu; Nguyen, Tran-Tien; Pham, Dinh-Luan; Nguyen, Binh-Hau (Peneliti Teknologi Teknik Indonesia, 2024)
Pendubot is a classical system with high nonlinearity used in researching control algorithms. The Pendubot has a single input and multiple outputs (SIMO) and is under-actuated. In this paper, the focus is on studying the application of the Particle Swarm Optimization (PSO) algorithm to find optimal parameters for the LQR controller. The results obtained by the PSO algorithm will be compared when running with different parameters. Evaluations of the performance when applying the PSO algorithm to find optimal parameters will be drawn based on simulation results in Matlab/Simulink and experimental outcomes with various scenarios.